ESTRATÉGIAS DE APRENDIZAGEM DE LÍNGUAS ESTRANGEIRAS – UM CAMINHO EM DIREÇÃO À AUTONOMIA - Silva, Walkyria Magno e (Intercâmbio, 2010)
This paper investigates the use of learning strategies by tutors, competent students and not so competent students involved in a research project. They wrote narratives of how they learned English, and the strategies reported were tabulated. Evidence shows the importance of the use of strategies, which points to a need of explicit teaching and discussing them in foreign language classes.